The nurse in indigenous health: a literature review (Research, Society and Development, 2021)
It is understood that, as well as those who are not indigenous, the indigenous population also has their rights to education, housing, leisure, as well as health, in accordance with the Federal Constitution of 1988. in indigenous health, with emphasis on nursing care in indigenous health services. Descriptive study, literary review, using articles from scientific journals in the health field, theses and dissertations, available at: SCIELO, LILACS, MEDLINE; in Portuguese, English and Spanish. Analyzed by the method of Bardin. The struggle for indigenous health in Brazil was legitimized with the creation of the Health Care Subsystem for Indigenous Peoples, through the Arouca Law. The professionals involved are defined according to the epidemiological situation, health needs, geographic characteristics, access and level of organization of services, respecting the ethnic specificities of each indigenous people, and must act in conjunction with other SUS services. The profile of the professional nurse, as well as his performance, is taking shape, according to the references found within the indigenous area in which he works, contributing to the consolidation of a care model that moves away from what is proposed. according to existing policy guidelines Nurses' knowledge of indigenous health is essential to offer quality care, however, a factor that should be taken into account is their experiences from the moment they begin to carry out their work together. to these populations.